2010
DOI: 10.1186/1742-6405-7-47
|View full text |Cite
|
Sign up to set email alerts
|

HIV, appendectomy and postoperative complications at a reference hospital in Northwest Tanzania: cross-sectional study

Abstract: BackgroundAppendicitis is a frequent surgical emergency worldwide. The present study was conducted to determine the prevalence of HIV, and the association of infection with clinical, intraoperative and histological findings and outcome, among patients with appendicitis.MethodsWe performed a cross sectional study at Weill-Bugando Medical Centre in northwest Tanzania. In total, 199 patients undergoing appendectomy were included. Demographic characteristics of patients, clinical features, laboratory, intraoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
41
9
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(71 citation statements)
references
References 23 publications
(30 reference statements)
10
41
9
11
Order By: Relevance
“…Gigabhoy et al (4) recently showed that the HIV prevalence in patients undergoing appendectomy at a large tertiary urban hospital is 28%. In a Tanzanian study conducted at a major referral centre, the prevalence was found to be 13.1% (6). These results support the theory that HIV status may be a risk factor for appendicitis (11,12).…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Gigabhoy et al (4) recently showed that the HIV prevalence in patients undergoing appendectomy at a large tertiary urban hospital is 28%. In a Tanzanian study conducted at a major referral centre, the prevalence was found to be 13.1% (6). These results support the theory that HIV status may be a risk factor for appendicitis (11,12).…”
Section: Discussionsupporting
confidence: 61%
“…In a prospective cohort study, ČaČala et al (16) showed that HIV status did not influence the outcome of general surgical procedures, and CD4+ count was not a prognosticator of total hospital stay, hospital mortality and severity of post-operative sepsis. However, in a recent large retrospective study investigating the effects of HIV status on the outcomes of surgical sepsis, Green et al (6) determined that there was a significantly higher mortality of 60% in patients who had a CD4+ count <200 cells/μl versus 2% in the CD4+ count >200 cells/μl group. In emergency surgery patients, a lower CD4+ count is associated with increased post-operative septic complications and longer hospital stay (14,15,17,19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations